Identification of potentially harmful microalgal species and eutrophication status update in Benoa Bay, Bali, Indonesia. (1st September 2021) - Suteja, Yulianto; Dirgayusa, I Gusti Ngurah Putra; Afdal; Cordova, Muhammad Reza; Rachman, Arief; Rintaka, Wingking Era; Takarina, Noverita Dian; Putri, Wike Ayu Eka; Isnaini; Purwiyanto, Anna Ida Sunaryo
Abstract: Harmful algal blooms (HABs) often occurred in a eutrophicated coastal areas, which causes ecological, economic, and health problems to the ecosystem and coastal communities. Benoa Bay is a coastal ecosystem in Indonesia which threatened by eutrophication and vulnerable to the occurrence of HABs in the future. This study focuses on identifying the potential harmful microalgal species and updating the trophic status in Benoa Bay. Sampling was done during the dry season in 2017 from 30 stations. Tewnty-nine species of phytoplankton were identified in Benoa Bay. Coscinodiscus spp., Pseudo-nitzschia spp., Skeletonema spp., Chaetoceros spp., Rhizosolenia spp., and Ceratium spp., were categorized as potentially harmful microalgal. Among those, Coscinodiscus spp. was the most abundant and widely distributed species in Benoa Bay. Phytoplankton cell density was highest in the area between Suwung Landfill and Floating Net Cage (16, 584 cells L -1 ), while the lowest (20 cells L -1 ) was found in the Sama River estuary. The tb-RDA analysis showed salinity and dissolved oxygen percentage saturation (D%O) were two most significant factor that drives the density and distribution of phytoplankton species in Benoa Bay. In general, Benoa Bay was in the oligotrophic state based on phytoplankton abundance and chlorophyll-a concentration, while in mesotrophic states based on TRIX. The occurrence of some potentially harmful microalgal species, along with relatively high trophic levels in Benoa Bay, requires serious attention to prevent damages from any HABs event in the future. Graphical abstract: Image 1 Highlights: The phytoplankton in Benoa Bay dominated (85.2%) by potentially harmful microalgal. The Coscinodiscus spp. was dominated and found in almost all observation sites. The phytoplankton abundance and chlorophyll-a concentration steeply increased to the mainland and estuary area. Based on TRIX, the trophic state in Benoa Bay ranged from 2.70 (oligotrophic) to 9.20 (hypertrophic) with an average of 4.89 + 1.61 (mesotrophic). TRIX in Benoa Bay was more influenced by chlorophyll-a and DIN than DIP and D%O.